PERCOBAAN BUNUH DIRI: TINJAUAN MEDIS, BIOETIK, HUMANIORA DAN PROFESIONALISME - Abrar, Hanan Khasyrawi; Putra, Bayu Pratama (Ensiklopedia of Journal, 2025)
Abstract: This study aims to examine the handling of attempted suicide cases from four main perspectives: medical, bioethical, humanities, and healthcare professionalism. This study uses a qualitative approach and normative-ethical literature review. Primary data were obtained through in-depth interviews with healthcare professionals experienced in treating patients who have attempted suicide. Meanwhile, secondary data were obtained from scientific literature, ethical documents, and relevant regulations. Data were analyzed thematically and normatively using bioethical principles such as autonomy, beneficence, non-maleficence, and justice and presented descriptively. The results show that healthcare professionals consistently face a dilemma between respecting patient autonomy and the professional obligation to prevent death. From a humanities perspective, suicide is often understood as an expression of existential suffering that requires an empathetic and reflective approach. Meanwhile, from a professional perspective, there is still a gap between ideal values and practice in the field, particularly regarding stigma, communication, and systemic support for patients and healthcare professionals.Keywords: Tentamen Suicide, Bioethics, Humanities and Professionalism.